Information Technology in Business Development Field - T Tawami; F B Febriana (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this paper is to explain business development by utilizing social media where it is in demand by many people. Using social media is one of the most effective ways to promote business development and to increase the awareness of it. The method used in this research was survey. The results of the survey were business development through social media has a good, economical and well-organized opportunity. The research was conducted by discussing the increase of business development using social media.